Control of the quality and homogeneity of halide perovskites by mixed-chloride additives upon the film formation process. Issue 33 (16th August 2021) - Zheng, Daming; Pauporté, Thierry
Abstract : The roles of mixed ammonium chloride and potassium chloride additives on the growth of Cs0.1 FA0.9 PbI3 perovskite film are investigated along with the surface treatment by an n -propylammonium iodide solution which produces an interfacial buffer layer. Abstract : Nowadays, overcoming the stability issue of perovskite solar cells (PSCs) while retaining high efficiency has become an urgent need for the future of this technology. By using X-ray diffraction (XRD), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC), and introducing solvent profile evolution monitoring by the glow discharge optical emission spectroscopy (GD-OES) technique, we have highlighted the effect of potassium chloride and ammonium chloride additives on the formation mechanism of Cs0.1 FA0.9 PbI3 films upon annealing. Two formation steps are distinguished: first, the superficial residual solvent is eliminated; second, the solvent in the depth of the film is evaporated. The elimination profile depicts the final morphology of the layer. The downward (top-down) growth has been encountered for the pristine and potassium chloride additive cases. It led to the formation of multiple boundaries and middle-sized grain morphology. We unveil that employing both potassium chloride and ammonium chloride additives forces the homogeneous elimination of the solvent across the layer, and thus the lateral growth of the grains. It resulted in large size, monolithic and defect-poor grains with good coverage of the substrate which are the targeted properties for high efficiency. By combining this approach with the film surface treatment with n -propylammonium iodide (PAI), further performance and stability increases have been achieved. It resulted in a stabilized power conversion efficiency over 21%. These PSCs are also proven to be highly resistant to external stressors such as light, moisture, and temperature.